Multiple mediated effect of adult attachment style on association between acquired skills from Gottman's intervention on marital communication patterns - Deylami, Neda; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2017)
This research aimed to evaluate the multiple mediated effect of adult attachment style on acquired skills of Gottman’s psycho-educational intervention and marital communication patterns in 144 married people selected from 256 Iranian spouses who had already finished the Gottman’s intervention within two months. The accumulated evidences have shown Gottman’s intervention improves marital communication patterns, what is missing, however, is the multiple mediated effect of adult attachment style on marital communication patterns and intervention. The results indicated that acquired skills of Gottman’s psycho-educational intervention significantly influenced all attachment’s subscales. Furthermore, attachment significantly mediated the effect of acquired skills of Gottman’s intervention on marital communication patterns. These results suggest family counselors to consider attachment style as predictable ways for more effective Gottman’s intervention on marital communication patterns. For future researches, it is suggested to utilize Actor-Partner Interdependence Model for Mediator for evaluating the multiple mediated effect of adult attachment in dyadic interaction.